Establishing structure-sensitivity of ceria reducibility: real-time observations of surface-hydrogen interactions. Issue 11 (10th February 2020) - Duchoň, Tomáš; Hackl, Johanna; Mueller, David N.; Kullgren, Jolla; Du, Dou; Senanayake, Sanjaya D.; Mouls, Caroline; Gottlob, Daniel M.; Khan, Muhammad I.; Cramm, Stefan; Veltruská, Kateřina; Matolín, Vladimír; et al.
Abstract : Unraveling the thermodynamic origin of the structure–reducibility of cerium oxide (100) and (111) surface planes. Abstract : The first layer of atoms on an oxide catalyst provides the first sites for adsorption of reactants and the last sites before products or oxygen are desorbed. We employ a unique combination of morphological, structural, and chemical analyses of a model ceria catalyst with different surface terminations under an H2 environment to unequivocally establish the effect of the last layer of atoms on surface reduction. (111) and (100) terminated epitaxial islands of ceria are simultaneously studied in situ allowing for a direct investigation of the structure–reducibility relationship under identical conditions. Kinetic rate constants of Ce 4+ to Ce 3+ transformation and equilibrium concentrations are extracted for both surface terminations. Unlike the kinetic rate constants, which are practically the same for both types of islands, more pronounced oxygen release, and overall higher reducibility were observed for (100) islands compared to (111) ones. The findings are in agreement with coordination-limited oxygen vacancy formation energies calculated by density functional theory. The results point out the important aspect of surface terminations in redox processes, with particular impact on the catalytic reactions of a variety of catalysts.